2014
DOI: 10.5935/0034-7167.20140004
|View full text |Cite
|
Sign up to set email alerts
|

Route taken by families of children hospitalized in a teaching hospital

Abstract: Estudo exploratório, descritivo, de abordagem qualitativa, desenvolvido com o objetivo de conhecer o itinerário percorrido pela família da criança internada em unidade hospitalar. Os dados foram coletados na unidade de internação pediátrica do Hospital Universitário Regional de Maringá (HUM), por meio de entrevistas semi-estruturadas junto aos acompanhantes, posteriormente submetidos a análise de conteúdo, originando duas categorias: O papel da família na identifi cação de desvios de saúde na criança, e o (Des… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2018
2018
2018
2018

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 14 publications
0
2
0
Order By: Relevance
“…Therefore, in this context, the nurse has the ability to provide effective care, through the nursing process, identifying health problems in the child, favoring, even, the early diagnosis of childhood cancer. It is known that the therapeutic pathway is involved by the planning and strategies that seek to solve the problems involving the patients' health, being essential the nursing performance in this process (12) .…”
Section: The Family Encounter With the (Un)preparation Of Professionamentioning
confidence: 99%
See 1 more Smart Citation
“…Therefore, in this context, the nurse has the ability to provide effective care, through the nursing process, identifying health problems in the child, favoring, even, the early diagnosis of childhood cancer. It is known that the therapeutic pathway is involved by the planning and strategies that seek to solve the problems involving the patients' health, being essential the nursing performance in this process (12) .…”
Section: The Family Encounter With the (Un)preparation Of Professionamentioning
confidence: 99%
“…Data from another research have shown that sometimes several health services have organized their work processes with a focus on the procedure rather than on the patient, leaving aside the qualified listening and prioritizing the performance of tests. The fulfillment of the health needs, when it is not effective, reflects in new actions, since families and the patient are led to seek other ways and services that can offer them access to the care they demand (12) .…”
Section: He Stopped Walking Could Not Even Stand Then I Went Crazymentioning
confidence: 99%